Antimicrobial and antioxidant activities of neem assisted silver-modified zeolite X synthesized from kaolin - Ralph Kwakye; Grace Boakye; Bright Yaw Vigbedor; Albert Aniagyei; Bernard Owusu Asimeng; Boniface Yeboah Antwi; David Neglo; Salifu Nanga (PLoS ONE, 2026)
Zeolite X was synthesized from kaolin and then modified using ( Azadirachta indica ) neem together with silver nitrate solution by ion exchange. X-ray diffraction confirmed a highly crystalline FAU framework characterised by a low angle reflection, which showed that silver incorporation did not alter the zeolite structure. Scanning Electron Microscopy (SEM) revealed a well-defined polyhedral crystal for zeolite X, whiles the Ag-zeolite X exhibited increased surface heterogeneity and agglomeration. Fourier Transform Infrared (FT-IR) and Raman Spectroscopy further confirmed framework retention, with band broadening attributed to the partial substitution of Na⁺ by Ag + within the zeolite lattice. The antimicrobial activity of zeolite X, Ag-zeolite X, were evaluated against Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Enterococcus faecalis, Candida albicans, Aspergillus niger strains by Minimum Inhibition Concentration (MIC) and Minimum Bacterial/fungal Concentration (MBC/MFC) Assays. The antioxidant properties were evaluated using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2’-Azino-bis (3-ethylbenzothialine-6-sulfonic acid (ABTS) radical scavenging assays. The unmodified zeolite X showed weak activity (MIC, MBC, MFC > 1 mg/mL, R > 4) whilst the Ag-zeolite X showed strong antimicrobial activity (MIC = 0.5–1.0 mg/mL, MBC, MFC = 0.5–2 mg/mL, R ≤ 4) across all tested strains. Antioxidant activity assessed using DPPH and ABTS radical scavenging assays showed significantly enhanced antioxidant performance for Ag-zeolite X compared to unmodified zeolite X, particularly in the ABTS assay. These findings demonstrate that neem-assisted silver modification enhances the bioactivity of kaolin-derived zeolite X while preserving its crystalline framework, supporting its potential application in biomedical, food packaging, and water treatment systems.